1993
DOI: 10.1136/adc.68.3.360
|View full text |Cite
|
Sign up to set email alerts
|

Snoring, sleep disturbance, and behaviour in 4-5 year olds.

Abstract: Parents of 996 children aged 4-5 years identified consecutively from the Oxford health visitor register were asked to complete a questionnaire about breathing disorders during sleep. A total of 782 (78.5%) was returned. Ninety five (12-1%) children were reported to snore on most nights. Habitual snoring was significantly associated with daytime sleepiness, restless sleep, and hyperactivity.The questionnaire responses were used to select two subgroups, one at high risk of a sleep and breathing disorder and a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
501
6
37

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 821 publications
(571 citation statements)
references
References 22 publications
27
501
6
37
Order By: Relevance
“…Aproximadamente 10% das crianças roncam durante o sono na maior parte da noite, sendo que estas na maioria das vezes apresentam ronco primário, que é definido como roncos durante o sono sem episódios de apnéia, hipoventilação ou hipóxia. Ali et al 24 (1993) observaram que 50% das crianças que apresentavam roncos aos 4 anos, referidos pelos pais, tiveram melhora sem nenhum tratamento após 2 anos de seguimento. Em contrapartida, cerca de 40% destas crianças com história de ronco noturno podem apresentar SAHOS 17,18 .…”
Section: Discussionunclassified
“…Aproximadamente 10% das crianças roncam durante o sono na maior parte da noite, sendo que estas na maioria das vezes apresentam ronco primário, que é definido como roncos durante o sono sem episódios de apnéia, hipoventilação ou hipóxia. Ali et al 24 (1993) observaram que 50% das crianças que apresentavam roncos aos 4 anos, referidos pelos pais, tiveram melhora sem nenhum tratamento após 2 anos de seguimento. Em contrapartida, cerca de 40% destas crianças com história de ronco noturno podem apresentar SAHOS 17,18 .…”
Section: Discussionunclassified
“…1,2,13 study also showed that although polysomnograhy provides much information about OSDs, it is unable to establish the degree of quality of life improvement following adenotonsillectomy, as perceived by parents.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that up to 3% of children have OSAHS, 1 and that a higher percentage has UARS. 2 OSDs cause a variety of physical conditions and affect the child's quality of life, leading to low weight gain, altered cranio-facial development, [3][4][5] cardiopulmonary sequelae, 3,4 behavioral changes, 3,4,6,7 and poor school performance, 8 all of which have been well documented.…”
Section: Introductionmentioning
confidence: 99%
“…Horlama basit benign bir rahatsızlık olarak kabul edilmekte ise de OSAS hayatı tehdit eden bir patolojidir ve tedavi edilmesi gerekmektedir. Sağlıklı çocuklarda OSAS görülme oranı %2 iken obez çocuklarda bu oran %37 ile %46 arasında değişmektedir 6,7 .…”
Section: Endikasyonlarunclassified